1982
DOI: 10.1149/1.2123601
|View full text |Cite
|
Sign up to set email alerts
|

Decapsulation and Photoresist Stripping in Oxygen Microwave Plasmas

Abstract: Oxygen microwave (mW) plasmas have been used to strip AZ 1350 J photoresist on glass substrates and to decapsulate hybrid resistor networks and Si IC packages. It has been found that the use of microwaves as the generating field provides an abundance of long‐lived atomic oxygen such that processing can be carried out in the afterflow of the discharge. In this downstream system, photoresist and organically based epoxy encapsulants were removed at rates of approximately 6.0 μm/min. In addition, optical emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 1 publication
2
25
2
Order By: Relevance
“…The degradation rates increase linearly with the applied power (P,) in both an oxygen and an argon plasma in agreement with those observed for many other polymers, 33,36,37 but extrapolation of these straight lines at P, = 0 do not go through zero. Then, the degradation rates versus power can be expressed by the following equation:…”
Section: Degradationsupporting
confidence: 86%
“…The degradation rates increase linearly with the applied power (P,) in both an oxygen and an argon plasma in agreement with those observed for many other polymers, 33,36,37 but extrapolation of these straight lines at P, = 0 do not go through zero. Then, the degradation rates versus power can be expressed by the following equation:…”
Section: Degradationsupporting
confidence: 86%
“…Kimura et al [10] and Carl et al [11] reported that highly exited O and O þ 2 exist in the plasma. Dzioba et al [12] also observed not only O and O þ 2 but also O þ . From these reports, it is supposed that the positive ions (O þ 2 or O þ ) created in the plasma region and then the positive ions existed in the bulk of the oxide prepare by ECR method.…”
Section: Discussionmentioning
confidence: 91%
“…In either case, the photoresist was likely to be subjected to the particles and radiation present in the discharge, both of which can assist in the oxidation of the material since it has an activation energy in the neighborhood of 0.5 eV (3,11). However, in our case, as in others (9,10,12), the circuits to be cleaned are separated from the environment of the discharge. This not only removes the materials from the possibly harmful effects of the discharge, but also allows better control of the process parameters owing to a better understanding of the various phenomena involved in the downstream reactions.…”
mentioning
confidence: 73%